High-quality chromosome-level genome assembly of Litsea coreana L. provides insights into Magnoliids evolution and flavonoid biosynthesis - Zhang, Baohui; Yao, Xinzhuan; Chen, HuFang; Lu, Litang (Genomics (San Diego, Calif.), 2022)
The magnoliid Litsea coreana has been the subject of a substantial amount of research owing to its production of many flavonoid metabolites, high food processing value, and a controversial phylogenetic position. For this study, we assembled a high-grade genome at the chromosome scale and annotation of L. coreana that was anchored to 12 chromosomes. The total genome was 1139.45 Mb, while the N50 scaffold was 97.18 Mb long. The analysis of phylogenetic trees constructed by different methods show that the phylogeny of Magnoliids is inconsistent, indicating that the differentiation process of monocots, eudicots, and Magnoliids still remains in dispute. An ancient whole-genome duplication (WGD) event was shown to have occurred before the Magnoliales and Laurels had differentiated. Subsequently, an independent WGD appeared in the Lauralean lineage. A total of 27 types of flavonoids were detected in all five tissues of L. coreana. Chalcone synthases (CHSs) that are responsible for production of flavonoids have been validated at the bioinformatics level. The retention of comparative genomic analyses of the CHS gene family showed that this family had contracted significantly in L. coreana. Our research further elaborated the evolution of Lauraceae and perfected the genetic basis of flavonoid biosynthesis in L. coreana. Provides evidence that determines the evolutionary status of Magnoliids. The chalcone synthase gene family was significantly contracted in Litsea coreana. •This is the first high-quality Litsea coreana genome we have known.•Provide evidence for determining the evolutionary status of Magnoliids.•Perfect the genetic basis of Lauraceae flavonoid biosynthesis.•The chalcone synthase gene family was significantly contracted in Litsea coreana.